Identification of Drug-Related Problems in Hypertension Comorbid Type 2 Diabetes Mellitus Patients at Primary Health Care Center Batununggal District Bandung - Vina Septiani; Pudjiastuti Kartidjo; Alfi Nurul Islamiyah; Abdul Aziz MSW; Iis Rukmawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Many factors can increase the risk of hypertension, one of which is diabetes mellitus. The study aims to provide an overview of Drug-Related Problems (DRPs) in patients with hypertension comorbid type 2 diabetes mellitus at Primary Health Care Center Batununggal District Bandung. This research was an observational study with retrospective data collection and descriptive analysis. Data were taken from patient prescriptions January-December 2019 period. The sample inclusion criteria are patients aged 30-75 years, patients diagnosed with hypertension comorbid type 2 diabetes mellitus, and patients treated in January-December 2019. The number of samples that met the inclusion criteria was 268 patients, of which 69 patients (25.75%) are male, and 199 patients (74.25%) are female. 164 patients (61.2%) are aged 60-75 years old. It is found that 1 case (0.37%) has the drug-related problem of drug overdose and as many as 34 cases (12.69%) have potential drug interactions.